Recent Advances in Nanoenzymes Based Therapies for Glioblastoma: Overcoming Barriers and Enhancing Targeted Treatment - Liyin Wang; Min Gu; Xiaoli Zhang; Tingting Kong; Jun Liao; Dan Zhang; Jingwu Li (Advanced Science)
Abstract Glioblastoma multiforme (GBM) is a highly aggressive and malignant brain tumor originating from glial cells, characterized by high recurrence rates and poor patient prognosis. The heterogeneity and complex biology of GBM, coupled with the protective nature of the blood–brain barrier (BBB), significantly limit the efficacy of traditional therapies. The rapid development of nanoenzyme technology presents a promising therapeutic paradigm for the rational and targeted treatment of GBM. In this review, the underlying mechanisms of GBM pathogenesis are comprehensively discussed, emphasizing the impact of the BBB on treatment strategies. Recent advances in nanoenzyme‐based approaches for GBM therapy are explored, highlighting how these nanoenzymes enhance various treatment modalities through their multifunctional capabilities and potential for precise drug delivery. Finally, the challenges and therapeutic prospects of translating nanoenzymes from laboratory research to clinical application, including issues of stability, targeting efficiency, safety, and regulatory hurdles are critically analyzed. By providing a thorough understanding of both the opportunities and obstacles associated with nanoenzyme‐based therapies, future research directions are aimed to be informed and contribute to the development of more effective treatments for GBM.